P5.106 Charting the Path For Human Papillomavirus (HPV) Vaccine Introduction in Kenya: Assessing HPV Vaccine Acceptability Among Caregivers and Opinion Leaders in Nyanza Province, Kenya. (13th July 2013) - Friedman, A L; Dunne, E; Onyango, K; Habel, M; Ford, J; Kinsey, J; Markowitz, L; Phillips-Howard, P; Laserson, K
Abstract : Background: Cervical cancer is the second most common cancer diagnosed, and the leading cause of cancer-related mortality among women in Kenya. Kenya's Ministry of Health has outlined new prevention strategies, including support for vaccination. Formative research is critical to identify information, mobilisation and communication needs for vaccine introduction. To inform vaccine mobilisation and communication efforts in Kenya, this study sought to explore HPV vaccine-related community knowledge, attitudes, beliefs, and acceptability. Methods: We conducted five focus groups (FG) among caregivers of girls aged 9–12 years (n = 56), and 12 interviews with community opinion leaders in four locations of Nyanza Province, Kenya. Information was collected about participant knowledge, attitudes and beliefs regarding vaccines, cancer, cervical cancer and HPV; and perceived benefits/barriers to HPV vaccination. FG transcripts and interview notes were reviewed and analysed by a team of four researchers using thematic content analysis. FG data were analysed using NVivo8, and concept matrices were used for interview notes. Results: Awareness of vaccines and cancer was high among caregivers and opinion leaders, but low for cervical cancer, HPV and HPV vaccines. Whereas cancer was feared as a fatal disease, vaccines were generally well accepted. Once informed, participants were eager to support HPV vaccination for their daughters/communities. Protection against cervical cancer was perceived as a key benefit. Potential barriers to vaccination included religious/cultural beliefs; confusion/suspicion about intended vaccination effort; and concerns about vaccine safety and side effects (infertility). Most believed these barriers could be overcome with effective community mobilisation/education. Conclusion: The success of an HPV vaccination programme will depend critically on information, communication and social mobilisation - not only for raising awareness of cervical cancer and the need for vaccination, but for preventing possible misconceptions and rumours from arising. Recommendations are made to inform Kenya's communication and mobilisation strategies in preparation for vaccine introduction.